Determinants of Contract Farming Adoption and its Impact on Productivity of Smallholder Cotton Producers in Tanzania - Nsimbila, Paul Maganga (International Journal of Social and Administrative Sciences, 2021)
The focus of this paper was on the determinants of contract farming adoption and its impact on productivity to smallholder cotton producers in Bunda District, Tanzania. A survey of 220 contract farmers and 194 non-contract farmers was done by the researcher through personally administered questionnaires. Results from the treatment effects model show that gender of household head, household head age, experience in cotton cultivation, obtaining loan from other sources, being wage-earner, owning cattle, and owning bicycle had influence on adopting contract farming. However, education of household head, household size, off farm activities, owning motorcycle and radio had no influence on adopting contract farming. With regard to impact of contract farming adoption to productivity of smallholder cotton farmers in the investigation region, findings show that there is insignificant impact due to late supply of inputs to farmers by ginners, sprayers were not given on loan basis to farmers for spraying their farms in order to control pests and cultivation service was provided at TShs. 30,000/= upfront which was not afforded by farmers. In this case, Tanzania Cotton Board (TCB) should launch major campaign to educate farmers and ginners on the advantages of contract farming, secondly, ginners should be instructed to supply inputs (cotton seed and pesticides) to farmers timely and lastly ginners should provide sprayers and cultivation services to farmers as agreed when signing contract. Otherwise, contract farming adoption for the purpose of increasing productivity will be a nightmare.